Regulasi Lingkungan dalam Pengendalian Emisi Karbon di Sulawesi Tenggara - Mardi, Mardi; Yathita Lubis, Sashika; Lateli, Ichsan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Global climate change caused by carbon emissions has become a serious challenge to sustainable development. This study aims to analyze the effectiveness of environmental regulations in controlling carbon emissions in Southeast Sulawesi and their juridical implications for the protection of the right to a healthy environment. This research employs a normative legal method using statutory, conceptual, and case approaches. The findings indicate that the effectiveness of environmental regulations is influenced by institutional capacity, legal substance, law enforcement, economic factors, and public legal awareness. Regulatory ineffectiveness results in violations of environmental rights, increased carbon emissions, and weakened legal certainty. The novelty of this study lies in the integration of environmental law analysis with a local Southeast Sulawesi perspective and the strengthening of economic-based policy instruments..